Solubility and solubility product phenomena: Papua senior high school students' mental model: Research Article - Albaiti, Albaiti; Jukwati; Lepa, Alex Agustinus (Journal of Turkish Science Education, 2022)
This study aimed at determining the category and analyzes the mental models of the students from three senior high school clusters (low, medium, high) on the solubility and solubility product topic, knowing students' opinions on chemistry subject, knowing learning methods and assessment that teacher used in solubility and solubility products learning. This topic includes 10 concepts, namely the concept of solubility, the effect of temperature on solubility, unsaturated solutions, saturated solutions, supersaturated solutions, solubility equilibrium, the relationship between solubility and solubility product constants, the effect of common ions on the solubility of insoluble salts, the effect of changing pH on solubility, and precipitation prediction. This study involved 122 senior high school students in Jayapura, Papua. The researchers applied the descriptive qualitative research method with the triangulation technique of collecting data by examining the apparent tendency of students to explore their mental models. The instruments were a test of the mental model (linking the macroscopic, submicroscopic, and symbolic level), the documentation of the teachers’ teaching tools, and the interview protocol. Data were analyzed inductively. Hence, the result of the study emphasized meaning rather than generalization. The result revealed that the students’ mental models vary. The majority of the students’ mental models of the high cluster are partial while the majority of the students’ mental models of the medium and low clusters are not intact. The learning of this topic needs to be designed by linking macroscopic, submicroscopic, and symbolic levels for holistic students' knowledge of chemistry.
Keywords: solubility and solubility product; Mental Models; three senior high school clusters